2015
DOI: 10.1186/s13756-015-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant and carbapenemase producing Enterobacteriaceae among patients with urinary tract infection at referral Hospital, Northwest Ethiopia

Abstract: BackgroundUpdates on the epidemiology of antibiotic resistance bacterial pathogens is important. This is because the spread of multidrug resistant enterobacteriaceae (MDRE) and recently carbapenemase producing enterobacteriaceae (CPE) have emerged as a major public health concern in patients with urinary tract infections (UTIs). This study is therefore, aimed to assess the prevalence and associated risk factors of MDR and CPE among patients with UTIs.MethodsA cross sectional study was conducted among 442 sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
71
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 24 publications
33
71
16
Order By: Relevance
“…Likewise, 62% prevalence of ESBL in Enterobacteriaceae was detected in Uganda [10]. However, a study in Ethiopia reported that all Enterobacteriaceae from urinary tract infections were ESBL-positive [11]. In this study, majority of (75–85%) Enterobacteriaceae from blood, CSF and wound isolates were ESBL producer.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Likewise, 62% prevalence of ESBL in Enterobacteriaceae was detected in Uganda [10]. However, a study in Ethiopia reported that all Enterobacteriaceae from urinary tract infections were ESBL-positive [11]. In this study, majority of (75–85%) Enterobacteriaceae from blood, CSF and wound isolates were ESBL producer.…”
Section: Discussionmentioning
confidence: 65%
“…coli were reported in Ethiopia [12, 13]. Conversely, 100% ESBL-producers were reported from urinary tract infection in Ethiopia [11]. These variations might be due to difference in methods of ESBL detection and types of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted in Gabon reported that 15.4 % of Enterobacteriaceae (and 49.4 % of all K. pneumoniae isolates) were ESBL producers [9]. Other available studies show a prevalence rate of ESBLs ranging from 4 % of Central African Republic [8] to 50 % of Tanzania [10,11]. General concepts for the treatment: importance of appropriate treatment, pharmacokinetic/pharmacodynamic (PK/PD) data, susceptibility test, and combination therapy There are a number of important issues for the reduction of mortality in patients with infections caused by MDR Enterobacteriaceae, including the underlying mechanism of resistance, the choice and timing of empiric or targeted treatment, dosing and infusion, duration of treatment, and monotherapy versus combination treatment [12].…”
Section: Epidemiology Of Multi-drug Resistant (Mdr) Enterobacteriaceamentioning
confidence: 96%
“…The range of clinical symptoms of the infection is different from asymptomatic bacteriuria to bladder inflammation, pyelonephritis, septic shock, and defects in several organs (1,2). Both hospitalacquired and community-acquired urinary tract infections can lead to serious complications such as urinary tract disorders, uremia, hypertension, and even death (3).…”
Section: Contextmentioning
confidence: 99%